Perspectives of patients with chronic gastrointestinal conditions and their carers on transition from paediatric to adult health care services: results of a pilot study. (4th April 2011) - Punaganti, V R K; Rao, N; Azaz, A; Sebastian, S; Ashok, D
Abstract : Introduction/aim: Transition from paediatric to adult health care settings has emerged as an important issue. There is limited data on the perspectives of patients with chronic gastrointestinal problems on the process of transition. We aimed to survey the perspectives of patients and their carers who attend our gastroenterology transition clinic. Methods: Semi structured questionnaires (open and closed questions), designed to be filled independently by patients and their carers were used. The items in the questionnaire were ranked using Likert scale from 1 to 5 with the anchor of 'not important' to 'very important' and 'essential'. The results are described as proportion of respondents. χ 2 Test and fisher's exact test were used where appropriate. Results: 25 patients and 23 of the respective carers completed the questionnaire. The proposed age for initiation of transfer discussion was 16 by majority of patients and 17 by parents; both groups felt age 18 as appropriate to complete transfer. Vast majority of patients (20/25) and carers (22/23) felt the facility of dedicated transition clinic as beneficial. Both patients and carers considered adequate transfer of clinical information between the paediatric and adult teams (mean scores 4.33 and 4.9 respectively) and ensuring full understanding of the condition and its treatment (mean scores 4.0 and 4.71 respectively) as the most important aspects in preparation (p=NS). In relation to disease status, both groups rated a controlled disease state as very important at the time of transfer. The average importance scores on concerns and anxieties regarding transition process varied between patients and their carers (see table 1 ). Conclusion: The results of our pilot survey describe the importance of both organisational and individual disease related factors for a successful transition from a user perspective. Considering these will be essential in developing and improving the transition services.